Chitosan and layered double hydroxide nanosheets composite-based triboelectric nanogenerators for energy harvesting and touch sensing applications - Chaturvedi, Ekta; Roy, Poulomi; Pal, Santanu; Hossain, Afrin; Ahuja, Mayank (ACS Applied Nano Materials, 2026)
The alarming coexistence of increasing energy demand and environmental concerns has raised the immediate need to find suitable alternative energy resources. This need drives the development of environment-friendly, highly efficient tribo electric nanogenerators (TENGs), which have already gained significant success in mechanical energy harvesting. However, it still possesses challenges like ultralow current, which restricts its extensive applications in the real world. This article proposed the innovative combination of advanced layered double hydroxides (LDH) as a nanofiller with sodium chloride ionic salt as a simple strategy to enhance the output current of biodegradable chitosan polymer-based triboelectric nanogenerators (CS-TENG). Polymer chitosan provides a flexible matrix with many active sites, while the addition of LDH effectively enhances the surface area and positively charged sites due to its inherently positively charged layered nanostructure. This combination, together with NaCl-induced ionization and enhanced interfacial polarization, leads to an overall increase in the output performance of TENG. The developed TENG generated an output voltage (V OC) and current (I SC) of 101.6 V and 55.42 mu A, respectively, with a maximum power density of 629.5 mW m-2 at an external load resistance of 10 K Omega. It had the capability to power small-scale electronics like a watch, a calculator, an alarm buzzer, etc. A touch-sensitive TENG-based door sensor was also developed, which was capable of lighting LEDs just by a simple push on the door. This work demonstrated a simple, promising method to explore the potential of environmentally friendly CS-based mechanical energy harvesters for practical applications.
Keywords: Chitosan; Composite; layereddouble hydroxides; touch sensing; triboelectric nanogenerators